Sex-Differences in Health-Related Characteristics of Senior Center Users: The VERISAÚDE Study - Lorenzo-López, Laura; López-López, Rocío; Maseda, Ana; Buján, Ana; Rodríguez-Villamil, José Luis; Millán-Calenti, José Carlos (Frontiers in Psychology, 2020)
Background: We explored sex-related differences in sociodemographic, medical, psychological and functional conditions in older adults attending to senior citizens’ centers. Material and Methods: An exploratory study was conducted as part of the VERISAÚDE project, a cross-sectional population-based study of individuals aged ≥65 years enrolled in senior community centers located in Galicia, Northwest of Spain (n=749). A comprehensive gerontological evaluation was used to assess the social, medical, psychological and functional characteristics of the sample. Results: Women presented a higher prevalence of frailty (p=.017), a higher risk of malnutrition (p=.029), more medication consumption (p=.002), and polypharmacy (p=.008), higher depressive scores (p=.007), and lower cognitive scores (p=.045) than men, who showed a higher prevalence of hearing impairment (p=.034), toxic habits (all ps=.0001), and comorbidity (p=.002), and better quality of life (p=.030) and social resources (p=.002). Participants considered that attending and being involved in senior centers has a positive influence on their health and promotes successful aging. Discussion: Important differences were found between women and men in health variables, suggesting that sex exerts a powerful influence on health status in older age. These differences should be identified and taking into account when designing interventions to promote active aging and to improve the quality of life of older adults. Taking a sex perspective during the evaluation process could lead to a higher number of older people being effectively treated in clinical practice.